Placental growth factor in beta cells plays an essential role in gestational beta-cell growth - Weixia Yang (BMJ Open Diabetes Research & Care, 2020)
ObjectivePancreatic beta cells proliferate in response to metabolic requirements during pregnancy, while failure of this response may cause gestational diabetes. A member of the vascular endothelial growth factor family, placental growth factor (PlGF), typically plays a role in metabolic disorder and pathological circumstance. The expression and function of PlGF in the endocrine pancreas have not been reported and are addressed in the current study.Research design and methodsPlGF levels in beta cells were determined by immunostaining or ELISA in purified beta cells in non-pregnant and pregnant adult mice. An adeno-associated virus (AAV) serotype 8 carrying a shRNA for PlGF under the control of a rat insulin promoter (AAV–rat insulin promoter (RIP)–short hairpin small interfering RNA for PlGF (shPlGF)) was prepared and infused into mouse pancreas through the pancreatic duct to specifically knock down PlGF in beta cells, and its effects on beta-cell growth were determined by beta-cell proliferation, beta-cell mass and insulin release. A macrophage-depleting reagent, clodronate, was coapplied into AAV-treated mice to study crosstalk between beta cells and macrophages.ResultsPlGF is exclusively produced by beta cells in the adult mouse pancreas. Moreover, PlGF expression in beta cells was significantly increased during pregnancy. Intraductal infusion of AAV–RIP–shPlGF specifically knocked down PlGF in beta cells, resulting in compromised beta-cell proliferation, reduced growth in beta-cell mass and impaired glucose tolerance during pregnancy. Mechanistically, PlGF depletion in beta cells reduced islet infiltration of trophic macrophages, which appeared to be essential for gestational beta-cell growth.ConclusionsOur study suggests that increased expression of PlGF in beta cells may trigger gestational beta-cell growth through recruited macrophages.